A human case of Hymenolepis diminuta infection in Nepal - Kunwar, C.B.; Subba, B.; Shrestha, M.; Chapagain, R.H.; Jha, B.; Subedi, J.; Blangero, J.; Blangero, S. Williams; Towne, B. (Journal of Institute of Medicine Nepal, 2007)
A case of Hymenolepis diminuta infection in human is reported. The patient was an 18 year old Nepalese female with an array of gastrointestinal symptoms. She was successfully treated with niclosamide. This report, for the first time; of H. diminuta in Jiri area confirms the possible distribution of this species in Nepal. Journal of Institute of Medicine Vol.27(3) 2005